Analysis of One-Way Traffic Engineering System on The Majalengka City Health Road Section (In Front Of Majalengka Hospital) - Rafiki Mawarid Ayswara; Jody Martin Ginting (Fakultas Teknik Sipil dan Perencanaan, 2025)
This study examines the implementation of a one-way traffic engineering system on the Health Road section of Majalengka City, specifically in front of the Majalengka Regional General Hospital (RSUD Majalengka). The aim of this research is to evaluate the impact of the one-way system on road performance, identify its strengths and weaknesses, and provide recommendations for improvements to optimize road utilization. This study uses traffic volume survey methods, side obstacle analysis, and qualitative assessment. The results show a significant improvement in traffic flow, with the road performance level increasing from